How Many Trauma Admissions Require Acute Trauma Team Interventions? - Bitter, Bradon; Terry, Amy; Helmer, Stephen; Quinn, Karson; Haan, James M (Kansas Journal of Medicine, 2024)
Introduction.  The purpose of this study was to determine the percentage of trauma patients who have been admitted and received intervention and, of these, which were performed by non-trauma specialists.Methods.  A retrospective chart review was performed on all adult patients presenting through the trauma service between January 2019 and June 2019.  The information collected included: demographics, trauma activation level, total interventions performed, interventions by the trauma team, interventions by the subspecialty teams, and isolated injuries (orthopedic, neurosurgery, and other).Results.  A total of 287 patients were reviewed.  One hundred eleven of these patients (38.7%) underwent operative intervention.  Seventy-five patients (26.1%) underwent operative intervention by the orthopedic surgery team.  Sixteen patients (5.6%) underwent operative intervention by the neurosurgery team.  Fourteen patients (4.9%) underwent operative intervention by other subspecialties.  Only 6 patients (2.1%) underwent operative intervention by the trauma team.Conclusions.  The collected data suggests that less than half of the patient population underwent intervention by a surgical team.  This data demonstrates the need to re-evaluate admission criteria for trauma patients.